Liquidity, money creation and destruction, and the returns to banking - Ricardo de O. Cavalcanti; Andrés Erosa; Ted Temzelides (European Central Bank (ECB), 2004)
We build on our earlier model of money in which bank liabilities circulate as medium of exchange, and investigate the provision of liquidity for a range of central-bank regulations dealing with the potential of bank failure. In our model, banks issue inside money under fractional reserves, facing the event of excess redemptions. They monitor the float of their money issue and make reserve-management decisions which affect aggregate liquidity conditions. Numerical examples demonstrate bank failure when returns to banking are low. Central-bank interventions, injecting more funds or making interest payments proportional to holdings of reserves, may improve banks' returns and society's welfare, followed by a reduction in bank failure.
Keywords: E4; E5; 330; liquidity; private money creation